Market or state : the regulation and practice of bankers' remuneration in the UK and China / Longjie Lu, University of Edinburgh. - Lu, Longjie, 1988- (Cambridge University, 2022)
This book investigates the pre-crisis practice of bankers' remuneration in the UK to provide evidence of the problems in practice. It critically analyses the regulatory initiatives implemented after the crisis and investigates the post-crisis practice to reflect the effects and problems of the regulation. The book also discusses the traditional administration of remuneration and political incentives in Chinese banks and the regulatory initiatives for reforming bankers' remuneration. It investigates the recent practices in major Chinese banks to reveal the problems of the regulatory initiatives and the impact of political incentives. It will help academics, researchers, students and practitioners develop a comprehensive understanding of the ongoing reform of bankers' remuneration in the UK and the uniqueness of banks' remuneration systems and incentive mechanisms in China. Furthermore, it provides theoretical insights into the differences between the two jurisdictions in their regulations and practices and the deep-seated reasons for the differences.